4x-2(x-3)=-9+5x-9

Simple and best practice solution for 4x-2(x-3)=-9+5x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-2(x-3)=-9+5x-9 equation:


Simplifying
4x + -2(x + -3) = -9 + 5x + -9

Reorder the terms:
4x + -2(-3 + x) = -9 + 5x + -9
4x + (-3 * -2 + x * -2) = -9 + 5x + -9
4x + (6 + -2x) = -9 + 5x + -9

Reorder the terms:
6 + 4x + -2x = -9 + 5x + -9

Combine like terms: 4x + -2x = 2x
6 + 2x = -9 + 5x + -9

Reorder the terms:
6 + 2x = -9 + -9 + 5x

Combine like terms: -9 + -9 = -18
6 + 2x = -18 + 5x

Solving
6 + 2x = -18 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
6 + 2x + -5x = -18 + 5x + -5x

Combine like terms: 2x + -5x = -3x
6 + -3x = -18 + 5x + -5x

Combine like terms: 5x + -5x = 0
6 + -3x = -18 + 0
6 + -3x = -18

Add '-6' to each side of the equation.
6 + -6 + -3x = -18 + -6

Combine like terms: 6 + -6 = 0
0 + -3x = -18 + -6
-3x = -18 + -6

Combine like terms: -18 + -6 = -24
-3x = -24

Divide each side by '-3'.
x = 8

Simplifying
x = 8

See similar equations:

| 13.3+7u=-4.2 | | 7+5p=6p | | 7+5(2x+3)-9= | | 3x+8x-2=108 | | 27=3u-15 | | 10m+8m=108 | | -12.72+(-1.008)-(-4.3)+9.17= | | 7w-11w=8 | | -14-(-50)=x/8 | | q+358=435 | | log2/log(1/4) | | 3v-13=35 | | 2x+28=4x+1 | | 13+7.1x=5(1.5x+2) | | 2-2x=-6+2x | | 5x-17=11x-11 | | 3x-79=-11x+131 | | 62=5u+12 | | -12+a=18 | | 0.42a=0.08a+0.75 | | X+14=22.6 | | 6-1/3x-3=-1/2x | | 42x^2+x=1 | | 3j-5=13 | | 1/4*12m | | 8x^2-6x-12=0 | | (143)(y)=6 | | 0.6x+11=0.8x-1 | | 9+2t=17 | | 9y-85=7(4+y) | | 14u=24+8u | | 4(x+3y+5)+2(x-1)= |

Equations solver categories